Hubungan Tingkat Stres Dengan Kualitas Tidur Pada Lanjut Usia Di Desa Tiniawangko Kecamatan Sinonsayang Kabupaten Minahasa Selatan - Saroinsong, Fira Takasili; Kundre, Rina M.; Toar, Juwita M. (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2023)
Abstract Background. Stress is an unpleasant condition in individuals where it can cause physical and psychological stress to individuals. Sleep is a state of unconsciousness when a person can be awakened with sensory stimuli or other stimuli and is a reparative, restorative, physiological and very important phenomenon for the body. Objective. To determine the level of stress and sleep quality in the elderly in Tiniawangko Village, Sinonsayang District, barbarslot South Minasaha Regency. Method This study used a cross-sectional study design where the population in this study were all elderly people in Tiniawangko Village, totaling 157 elderly people. The sampling technique used the Total Sampling Technique with inclusion criteria, namely the elderly aged 60 years and over and able to communicate well, while the exclusion criteria were the elderly who were addicted to drugs and the elderly who suffered from mental disorders. The instruments used for stress levels used the DASS questionnaire and for sleep quality used the PSQI questionnaire. The results of the static test study with (p – 0.000 or p<0.05) showed a value of p = 0.003 with Ho rejected and Ha accepted. Discussion There is a significant relationship between stress levels and sleep quality in the elderly in Tiniawangko Village. The conclusion is that there is a relationship between stress levels and sleep quality in the elderly. Keywords: Stress levels; Quality of Sleep; Elderly